Influence Free Cash Flow and Growth Opportunity against Company Values with leverage as a Variable Intervening - Agostinho Pinto Soares; Muchlis Mas'ud; Alfiana (Optima Science, 2023)
The purpose of this research is to test and analyze the effect free cash flow and growth opportunities to company value with leverage as a variable intervening in textile and garment companies on the IDX in the 2019-2022 period. In this study the approach used by researchers is quantitative research and uses statistical formulas to help analyze the data and facts obtained. This data collection uses secondary data which can be taken from the Textile and Garment Sector companies listed on the IDX in the 2019-2022 period. The research model used ispath analysis. Data processing path analysis using program assistance IBM SPSS Statistics 25. The research results conclude Free Cash Flow not able to affect the value of the company (PBV), Free Cash Flow able to influence Leverage (THE), Growth opportunity (PER) is able to affect the value of the company (PBV), Growth opportunity (PER) is not able to influence leverage (THE), Leverage (DER) is not able to affect the value of the company (PBV), Leverage (DER) is not able to mediate the relationship between free cash flow to firm value (PBV), Leverage (DER) is not able to mediate the relationship between Growth Opportunity (PER) to firm value (PBV).